Pseudo‐Meigs' syndrome associated with hydropic degenerating uterine leiomyoma: A case report. Issue 4 (26th February 2014) - Oguma, Tomoko; Yamasaki, Noriyuki; Nakanishi, Kentaro; Kinoshita, Dan; Mitsuhashi, Tamae; Nakagawa, Shoko
Abstract Pseudo‐Meigs' syndrome secondary to uterine leiomyoma is a rare entity. A 50‐year‐old Japanese woman presented with a 3‐month history of shortness of breath. Chest X‐ray and magnetic resonance imaging revealed massive right pleural effusion, ascites and a large subserosal uterine myoma. She underwent a total abdominal hysterectomy with bilateral salpingo‐oophorectomy. The pathology was consistent with a benign leiomyoma. The ascites and pleural effusion rapidly disappeared postoperatively. The serum interleukin‐6 level was 3.9 pg/mL before surgery and declined to 1.6 pg/mL postoperatively. Previous published work has demonstrated that vascular endothelial growth factor and interleukin‐6 may play a role in the pathogenesis of Meigs' syndrome and that vascular endothelial growth factor may contribute to the development of pseudo‐Meigs' syndrome due to metastatic ovarian cancer. This is the first English‐language study showing the possibility that interleukin‐6 is relevant to the pathogenesis of pseudo‐Meigs' syndrome caused by degenerating uterine leiomyoma.